AB0450 The dark side of glucocorticoid therapy in systemic lupus erythematosus: can we do something about that?. (15th June 2017) - Saulescu, I; Gudu, T; Neagu, A; Opris, D; Borangiu, A; Daia-Iliescu, S; Groseanu, L; Balanescu, A; Bojinca, V; Ionescu, R
Abstract : Background: Corticosteroids are still one of the main treatment in Systemic Lupus Erythematosus (SLE). Beside the effect on controlling disease activity, they are also implicated in damage accrual. Both patients and physicians are some time afraid to adopt a steroid free regimen when possible. Objectives: To evaluate the knowledge and perception of patients with SLE upon glucocorticoids. Methods: 84 patients with SLE were evaluated and data about demographic, clinical, serological characteristics or treatment were collected. Presence of steroids related side effects like hypertension, osteoporosis, cataracts or diabetes mellitus were also assessed. All patients completed a questionnaire in order to evaluate patient's knowledge about steroids. They were asked if they had a discussion with the doctors about corticotherapy and side effects related to them, if they consider that this treatment could be stopped with specialist approval. Statistics was performed with SPSS program. Results: All patients had treatment with corticosteroids during disease evolution. 57.14% of them experienced at least one steroids related side effect. This patients were significant older: mean age at evaluation 49.50 versus 36.47 (p<0.0001), had a longer disease duration: mean SLE duration 9.27 versus 4.69 (p0.016), a higher mean Prednisone equivalent dose: 8.86 versus 4.71 (p 0.031), a higher mean SLICC Damage Index: 1.53 versus 0.44 (p 0.001) than patients without steroids related side effects. This complications were significantly more rare in patients that were on a steroid free regimen at the moment of evaluation versus those on a continuum steroid regimen (7.14% versus 50%, p<0.0001). When patients were asked if they will stop steroids according to medical advice, almost 1/3 of patients - 28.57% - responded "no- to afraid to do that". Patients willingness to adhere to a steroid free regimen in the future according to a physician recommendation was significant more frequent in younger patients (p 0.031, r -0.235), in those with steroids initiated in less than 1 year (p 0.016, r -0.297) and in those with less damage accrual (p 0.017, r-0.267). Flare at the moment of evaluation significantly reduced this possibility, at least from the patient perspective (p0.041, r 0.224). The likelihood of a future steroid free regimen was increased by a previous discussion patient-doctor about steroids (p0.002). Conclusions: This study clearly shows that an open discussion with our SLE patients about corticosteroids is mandatory from the beginning. Patients should be informed about possibility of a steroid free regimen when disease status permits. This will increase patient willingness to get free of steroids when possible, helping physician to limit the continuum damage accrual of SLE patients. References: Duru N, van der Goes MC, Jacobs JWG et al, " EULAR evidence-based and consensus-based recommendations on the management of medium to high-dose glucocorticoid therapy in rheumatic diseases", Ann Rheum Dis 2013; 72: 1905–1913. Disclosure of Interest: None declared